Program pembelajaran bagi peserta didik autis di Raudhatul Athfal Maestro NU Purbalingga - Muayyadah, Muayyadah (Piramida Akademi, 2024)
The study conducted at Raudhatul Athfal NU Maestro Purbalingga outlines the learning program for autistic students in group A as well as the problems faced by teachers in the 2022/2023 school year. This type of research is descriptive qualitative. The subjects of this study consisted of a class teacher and a group A student who had been detected as autistic. Data collection was done through interviews and observations. The data obtained was tested for validity by increasing persistence, triangulation, and using reference materials. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. Without special preparation, autistic students joined their classmates. Teachers use various learning approaches, such as games and movements, and adjust their schedules accordingly. Due to limited electronic means, learning media is more traditional. Standardized adjustments for autistic children are used to conduct holistic evaluations. The absence of special preparation, the absence of a dedicated space, and the difficulty of handling and evaluating autistic students, which interferes with the overall learning process, are the main obstacles.